Comparison of the sex-specific associations between systolic blood pressure and the risk of cardiovascular disease: A systematic review and meta-analysis of 124 cohort studies, including 1.2 million individuals - Peters, S.; Huxley, Rachel; Woodward, M. (2013)
Background and Purpose - Conflicting results have been reported on whether the association between increments in systolic blood pressure (SBP) and cardiovascular disease differs between men and women. We performed a systematic review with meta-analysis to compare reliably sex-specific associations between SBP and cardiovascular risk. Methods - PubMed MEDLINE was systematically searched for prospective population-based cohort studies published between January 1, 1966, and March 31, 2012. Studies were selected if they presented sex-specific estimates, with associated variability, of the relative risk for either ischemic heart disease or stroke according to SBP. The data were pooled using random effects models with inverse variance weighting, and estimates of the ratio of the relative risks per 10 mm Hg increment in SBP, comparing women with men, were derived. Results - Data from 124 prospective cohort studies, including information on 1197 472 individuals (44% women) and 26 176 stroke and 24 434 ischemic heart disease events, were included. Overall, there was no evidence to suggest a sex difference in the relationship between SBP and either the risk of stroke (pooled ratio of relative risks, 0.98 [95% confidence interval, 0.96; 1.01]; P=0.13) or ischemic heart disease (pooled ratio of relative risks, 1.00 [95% confidence interval, 0.97; 1.04]; P=0.85). Conclusions - Elevated levels of SBP are a major risk factor for stroke and ischemic heart diseases in both women and men. This study unequivocally demonstrates the broadly similar impact of SBP increments on cardiovascular outcomes in both sexes. © 2013 American Heart Association, Inc.